An Algorithmic Programming Approach for Back Pain Symptoms in Failed Back Surgery Syndrome Using Spinal Cord Stimulation with a Multicolumn Surgically Implanted Epidural Lead: A Multicenter International Prospective Study. Issue 3 (27th February 2014) - Rigoard, Philippe; Jacques, Line; Delmotte, Alexandre; Poon, Katherine; Munson, Russell; Monlezun, Olivier; Roulaud, Manuel; Prevost, Audrey; Guetarni, Farid; Bataille, Benoit; Kumar, Krishna
Abstract Introduction Many studies have demonstrated the efficacy and the medical/economic value of epidural spinal cord stimulation for the treatment of "failed back surgery syndrome" (FBSS). However, the back pain component of FBSS has been recalcitrant. Recent clinical trials have suggested that multicolumn surgically implanted leads combined with enhanced programming capabilities in the newer implantable pulse generators demonstrate the ability to treat the back pain component of FBSS. The objective of our present international multicentre study is to prospectively evaluate these findings in a larger population. Methods We conducted a prospective, nonrandomized, observational study on 76 patients with refractory FBSS, consecutively implanted with multicolumn spinal cord stimulation (SCS) between 2008 and 2011 in three neurosurgical pain management centers (Poitiers, France; Montréal, Canada; and Regina, Canada). The primary objective of this study was to prospectively analyze the effect of multicolumn lead programming on paresthesia coverage for the back pain region in these patients. The secondary objective was to assess the analgesic efficacy of this technique on the global and back pain components. Results Paresthesia could be induced in the lower extremities in the majority of patients with at least one of the configurations tested. Bilateral low back paresthesia was induced in 53.5% of patients, while unilateral low back paresthesia was induced in 78.9% of patients. Multicolumn configurations were statistically more effective than monocolumn configurations for all anatomic regions studied. At 6 months, 75.4% of patients receiving multicolumn stimulation (n = 57) obtained at least a 30% improvement of the back pain VAS score, while 42.1% of patients obtained at least a 50% improvement of the back pain VAS score. Conclusion This study confirms the hypothesis that multicolumn SCS should be considered as an important tool in the treatment of radicular and axial pain in FBSS patients. The efficacy of this modality is based on a rigorous patient selection process, access to new generation lead technologies, but most importantly an algorithmic programming approach for optimal stimulation and electrical field shaping. With over 40 million potential programming combinations associated with 16 contact leads to achieve paresthesia coverage, optimal stimulation is often missed as either the patient or the clinician become exhausted or overwhelmed during the course of therapy programming and optimization session.